Archaeology of identity and dissonance - George, Diane F.; George, Diane F.; Kurchin, Bernice; Kurchin, Bernice (University Press of Florida, 2019)
This book employs the discipline of historical archaeology to study this process as it occurs in new and challenging environments. It tackles these questions not only in multiple dimensions of earthly space but also in a panorama of historical time. The book seeks to make the study of the past relevant to our globalized, post-colonized, and capitalized world